Decentralization, Vertical Fiscal Imbalance, and Political Selection - Massimo Bordignon; Matteo Gamalerio; Gilberto Turati (Università Cattolica del Sacro Cuore, Dipartimento di Economia e Finanza (DISCE), 2013)
In a career-concern model of politics with endogenous candidacy and different types of politicians, following a decentralization reform, politicians with different skills are elected in municipalities characterized by different levels of autonomous resources. As an effect, consumer welfare increases only, or mainly, in richer municipalities. We test these predictions by exploiting the differentiated reduction in Vertical Fiscal Imbalance in Italian municipalities, due to the strong difference in the tax base, following the decentralization reforms of the '90s. Results strongly support our predictions and are robust to several alternative stories.
Keywords: D72; D78; 330; decentralization; vertical fiscal imbalance; quality of politicians